Strengthening Welfare-Oriented Local Regulation Through Deliberative Policy: Evidence From Nagari Singguliang Lubuk Alung, Indonesia - Zikri Alhadi; Rahmadani Yusran; Fitri Eriyanti; Hasbullah Malau; Hendri Satria; Suryanef; Karjuni Maani (Indonesian Journal Publisher, 2026)
This study examines how deliberative policy strengthens welfare-oriented local regulation in Nagari Singguliang Lubuk Alung, West Sumatra, Indonesia. The novelty of the study lies in integrating deliberative policy analysis, village-level policy capacity, and the distinctive institutional setting of Nagari governance, where formal village authority intersects with customary legitimacy and community-based public reasoning. Using a qualitative case-study design, the study draws on semi-structured interviews, focus group discussions, and document analysis, which were interpreted through an NVivo-informed thematic procedure. The findings show four concrete results. First, the main weakness of Nagari regulation is not the absence of formal authority, but the limited capacity to translate authority into legally coherent policy instruments. Second, stakeholder inclusion remains uneven) (customary leaders, religious figures, women representatives, youth, and community groups are recognized as important, but they are not yet systematically connected to policy drafting. Third, monitoring and feedback mechanisms remain weak, limiting policy learning after regulations are enacted. Fourth, deliberative policy is most needed in three welfare domains: peace and public order, community economic empowerment, and environmental cleanliness and sustainability. The study concludes that welfare-oriented local regulation requires simultaneous strengthening of legal drafting competence, participatory design, institutional coordination, and continuous policy learning.